2003
DOI: 10.1002/jcp.10352
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase type plasminogen activator receptor is involved in insulin‐like growth factor‐induced migration of rhabdomyosarcoma cells in vitro

Abstract: Urokinase-type plasminogen activator (uPA) binds to its receptor, uPAR, on the surface of cancer cells, leading to the formation of plasmin. Rhabdomyosarcoma (RMS) cell lines secrete high levels of insulin-like growth factor II (IGF-II), suggesting autocrine IGFs play a major role in the unregulated growth and metastasis of RMS. In vitro, IGF-II and IGF-I increased migration of RD cells to 124+/-9% (P<0.01) and 131+/-8% (P<0.05) of control, respectively. IGF-II-induced migration was abolished by insulin-like g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 37 publications
(40 reference statements)
1
12
2
Order By: Relevance
“…IGFBP-6 does not have an RGD sequence, but it contains a heparin binding domain and so can bind to glycosaminoglycans (36). Interestingly, our previous studies investigating the role of IGFBP-6 in migration using a wound assay showed that IGFBP-6 inhibited migration in an IGF-II-dependent manner (13), which conflicts with the results presented here. However, dual IGF-dependent and IGF-independent actions have previously been showed for other IGFBPs.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…IGFBP-6 does not have an RGD sequence, but it contains a heparin binding domain and so can bind to glycosaminoglycans (36). Interestingly, our previous studies investigating the role of IGFBP-6 in migration using a wound assay showed that IGFBP-6 inhibited migration in an IGF-II-dependent manner (13), which conflicts with the results presented here. However, dual IGF-dependent and IGF-independent actions have previously been showed for other IGFBPs.…”
Section: Discussioncontrasting
confidence: 99%
“…As shown in Fig. 5, IGF-II stimulated cancer cell migration, consistent with previous findings (13,25). Surprisingly, treatment with either wtIGFBP-6 or mIGFBP-6 (1 g/ml) also significantly increased migration in RD cells (Fig.…”
Section: Igfbp-6 Induces Tumor Cell Migration In An Igf-independentsupporting
confidence: 90%
See 1 more Smart Citation
“…As seen in many other cell lines with dysregulated IGF-I signaling, rhabdomyosarcoma cells are extremely susceptible to rapamycin in growth inhibition (IC 50 ¼ 1-3 nM) (Hosoi et al, 1998). Since IGFs (IGF-I and IGF-II) promote the motility of rhabdomyosarcoma cells (El-Badry et al, 1990;Minniti et al, 1992;Gallicchio et al, 2003), we determined whether rapamycin also inhibits motility of rhabdomyosarcoma cells. Using the wound-healing assay, we found that Rh1 and Rh30 (two rhabdomyo-sarcoma cell lines) migrated under autocrine (serum free) conditions as RD (another rhabdomyosarcoma cell line) cells did (El-Badry et al, 1990).…”
Section: Resultsmentioning
confidence: 91%
“…IGF-IR controls lung carcinoma cell motility and invasion by coordinately regulating expression and activation of matrix metalloproteinase-2 (Zhang and Brodt, 2002). IGFs are also potent stimulators of rhabdomyosarcoma cell motility (El-Badry et al, 1990;Minniti et al, 1992;Gallicchio et al, 2003). Therefore, IGF-I signaling contributes to metastatic phenotypes in various types of tumors.…”
Section: Introductionmentioning
confidence: 99%